Ortostaticheskoe testirovanije v otsenke funktsionalnoj gotovnosti junych sportsmenov - Korneyeva, I. T.; Polyakov, S. D. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The optimization of functioning of the blood circulation apparatus is the necessary condition for the achievement of high sports results. One of the methods for revealing of the latent changes in the cardiovascular system and in the mechanisms of regulation in particular is the orthostatic testing. 184 young athletes aged 11-14 years engaged in sports swimming were surveyed. The sports experience of children was 1-5 years, sports qualification - from the 3-rd adult category up to the candidate sports master. The orthostatic testing allows to estimate both reserve opportunities of system of regulation of blood circulation, and adaptable opportunities of young athletes organism. The basic variants of vegetative reactance - asympatheticotonic, sympatheticotonic and normotonic were found when orthostatic testing. Young athletes with hyperkinetic type of blood circulation can be considered as insufficiently adapted to the work for endurance, and at revealing the infringement of processes of repolarization a myocardium to attribute them to a group of risk.